HEALTH EDUCATION INNOVATION TRAINING FOR PATIENTS WITH DM WITH WHATSAPP GROUP MEDIA AT ABDOEL WAHAB SJAHRANIE HOSPITAL (Jurnal Abdimas Administrasi Kesehatan, 2021)
Various ways of conveying information about DM, including through the delivery of health education with counseling. Counseling with the lecture method is the method that is most often carried out and is limited by time, but WhatsApp media is a medium of communication that is used daily by many people in almost all countries. The messages sent can be in the form of written messages, pictures or sound so that this media is very suitable to be used as a media for health education in order to increase public knowledge in general and especially in patients with DM. The conclusion in this dedication is that there is an increase in the knowledge of patients with DM after training.